Effect of Time and Rate of Fertilizer Application on Nutrient Uptake by Wheat from Kufra Desert Soil - EL-SHARKAWY, M. A.; SGAIER, K. (The Libyan Journal of Agriculture, 2023)
A field trial was conducted in the Kufra desert to determine the response of the dwarf wheat to fertilizer treatment before and after planting. Leaf contents of potassium (K), nitrogen (N). phosphorus (P). Zinc (Zn). protein and chlorophyll were estimated. Although no K was added to the Kufra virgin soil, plant leaves contained relatively high K (1.1 to 1.9 %). I n absence of phosphorus fertilizer, wheat plants were stunted and tended to accumulate higher levels of nutrients. Chlorophyll content increased in phosphorus-deficient plants that received ammonium sulfate-N. Uptake of ammonium sul-fate-N was more efficient than Urea-N. Losses from Urea-N under Kufra conditions were apparently high. Zinc and phosphorus have to be added because of their low level in Kufra Soil.